Temporary duodenal stenting as a bridge to ERCP for inaccessible papilla due to duodenal obstruction: a retrospective study - Donatelli, Gianfranco; Cereatti, Fabrizio; Dumont, Jean-Loup; Dhumane, Parag; Tuszynski, Thierry; Derhy, Serge; Meduri, Alexandre; Vergeau, Bertrand Marie; Meduri, Bruno (Endoscopy International Open, 2016)
Background and study aims: Duodenal obstruction may prevent performance of endoscopic retrograde cholangiopancreatography (ERCP). Percutaneous transhepatic biliary drainage (PTBD) or Endoscopic ultrasonograhy-guided biliary access (EUS-BD) are alternative treatments but are associated with a higher morbidity and mortality rate. The aim of the study is to report overall technical success rate and clinical outcome with deployment of temporary fully or partially covered self-expanding duodenal stent (pc/fcSEMS) as a bridge to ERCP in case of inaccessible papilla due to duodenal strictures.Patients and methods: This retrospective study included 66 consecutive patients presenting with a duodenal stricture impeding the ability to perform an ERCP. Provisional duodenal stenting was performed as a bridge to ERCP. A second endoscopic session was performed to remove the provisional stent and to perform an ERCP. Afterward, a permanent duodenal stent was delivered if necessary. Results: Sixty-six duodenal stents (17 pcSEMS and 49 fcSEMS) were delivered with a median indwelling time of 3.15 (1 – 7) days. Two migrations occurred in the pcSEMS group, 1 of which required lower endoscopy for retrieval. No other procedure-related complications were observed. At second endoscopy a successful ERCP was performed in 56 patients (85 %); 10 patients (15 %) with endoscopic failure underwent PTBD or EUS-BD. Forty patients needed permanent duodenal stenting. Conclusions: Provisional removable covered duodenal stenting as a bridge to ERCP for duodenal obstruction is safe procedure and in most cases allows successful performance of therapeutic ERCP. This technique could be a sound option as a step up approach before referring such cases for more complex techniques such as EUS-BD or PTBD.